Zéolitas ZSM-12 mesoporosas textura, cristalinidade e atividade ácida para o craqueamento de cicloexano - Carvalho, Kele Tatiane Gomes (2013)
The research addressed the generation of mesoporosity in the zeolite ZSM-12 (MTW). In the first part we studied the synthesis of ZSM-12 via conventional methodology and in the presence of a mesopore directing agent, organosilane [3-(Trimethoxy-silyl)propyl] octadecyldimethylammonium chloride (TPOAC). It was verified to influence the TPOAC/SiO2 and H2O/SiO2 ratios and, also the aging of the reaction mixture, temperature and time of the hydrothermal treatment. In the second part we studied the formation of mesoporosity by post-synthesis treatment with alkaline solution (NaOH). For optimization of such treatment the concentration of the NaOH solution and the temperature were varied. The zeolites were characterized by X-ray diffraction, chemical analysis by energy-dispersive X-ray spectroscopy, N2 adsorption/desorption, scanning electron microscopy, nuclear magnetic resonance of 27Al, and temperature-programmed desorption of ammonia. By the analyses of X-ray diffraction and Rietveld refinement, we verified a decrease in crystallization kinetics with increasing TPOAC/SiO2 ratio and a tendency for simultaneous crystallization of MFI and MTW phases with increasing H2O/SiO2 ratio, temperature and aging time. It was possible to obtain mesoporous ZSM-12 with high purity and crystallinity with only small quantities of TPOAC and relatively long crystallization times. For ZSM-12 zeolites treated in basic medium, there was the formation of mesopores in the range from 2.9 to 23 nm due to the silicon extraction from the crystalline framework, which caused a decrease in the volume of micropores and an increase in the total acidity, assigned to the decrease in Si/Al ratio. In the cracking of cyclohexane at 400 °C, although the presence of mesoporosity had caused a decrease in the total acidity, the zeolites synthesized with TPOAC showed similar conversions to conventional zeolite with minimal catalytic deactivation, which was attributed to the better mass transfer and less coke formation. The ZSM-12 zeolites treated with NaOH exhibited activity and stability similar to those obtained in the presence of TPOAC. By its higher proportion of strong acid sites, the conventional ZSM-12 zeolite showed higher hydrocarbon yields in the range from C2 to C4 in comparison with the mesoporous zeolites, with the latter showing a higher yield for C6 hydrocarbons.